Higher Order Thinking Questions in Teaching Reading in a Private Primary School - Mintre, Rosalinda; Lie, Anita (Beyond Words, 2020)
In order to meet up the needs of acquiring the 21st century skills, students need to be equipped with critical thinking skills. In English language learning, one way to foster students’ critical thinking is through Higher Order Thinking (HOT) questions in reading. This study unveils the implementation of HOT questions in Grade 5 reading classes in a private primary school in Surabaya. The study in particular was aimed to find out (1) the structure of the teacher’s questions, (2) the types of the teacher’s questions, and (3) the students’ responses. This study used the New Bloom’s taxonomy as the underlying instrument for classifying the types of questions and the students’ responses. Four class observations, four teacher’s interviews and two students’ focus group discussions were conducted in this study. The recorded data were transcribed and analyzed to get the results. The results of the data analysis indicate that 65.15% of the total of 66 questions used by the teacher in the classroom were HOT questions. Among all types of HOT questions, the New Bloom’s analyze questions were used the most with 37.88% of the total questions. HOT questions were mostly addressed during the whilst-instructional activities. Interestingly, the HOT questions were answered in different forms: oral answers, dramatizations and presentations. Related to this finding, the teacher was quite satisfied with the students’ responses since they reached the same thinking level, although sometimes it is necessary for the teacher to simplify his questions in order to get students’ responses.